Analisis Kemampuan Siswa Dalam Menyelesaikan Soal Cerita Pokok Bahasan Program Linear - Herlina Ahmad; Nurhidayah Nurhidayah; Nurdin Nurdin (Jurnal MathEducation Nusantara, 2018)
Abstract The main problem in this study is the number of students who feel overwhelmed in solving math problems, especially in the form of story problems on the subject linear program. So this study aims to determine the students' traits in solving the story problem on the subject of linear programming, through research "Descriptive Qualitative". The subject of this research is the students of class XI SMK Ma'arif Husnul Khatimah. Data were collected using observation, test and interview methods. Furthermore, the data obtained are then analyzed, based on qualitative data analysis through 3 stages of flow ie data reduction, data presentation and verification and conclusion drawing. The results showed that, of the total 6 students who were subjected to the study, most (4 students) were unable to achieve the four aspects of capability observed in this study. The other 2 students, each capable of working on the problem up to the aspects of ability 1 understand the problem) and aspects of ability 2 (make a plan of completion). As for the aspect of ability 3 (executing the completion plan) and the ability aspect 4 (interpreting the results obtained), no students are able to do the problem up to two aspects of this ability. Based on the results of the nalysis of student answers at the time of the test and interview, it can be seen that because of the inability of students understand the problem given is to write things that are known and asked and make the pemisalan, thus causing students constrained in the next step Keywords: Ability, Linear Program, Story Problem